Investigating undergraduate students’ engagement in systems thinking and modeling using causal maps - Sabel, Jaime L.; Zangori, Laura; Parsley, Kathryn M.; Sous, Sedra; Koontz, Jason (Frontiers in Education, 2023)
To develop a foundation of scientific understanding, undergraduate biology students need to integrate ideas about individual concepts into thinking about complex biological systems. To investigate the extent to which undergraduate students engage in systems thinking, we conducted a pre-post study with students in a required undergraduate botany course at a small liberal arts college in the Midwest. All students in the study completed a causal map at the beginning and end of the course. Casual maps are similar to concept maps but demonstrate cause and effect relationships rather than other connections included in a concept map. This work highlights the difficulties undergraduate students have with engaging in systems thinking but provides important insight into the particular areas in which students do engage in more complex thinking and areas in which we can specifically target with instruction and intervention.